Endometriosis Cell Spheroids Undergo Mesothelial Clearance in a Similar Manner to Ovarian Cancer Cell Spheroids - Allison A. Kloeckner; Sarah R. Walker (Cells)
Endometriosis is a gynecological disease characterized by the presence of endometrium-like cells located outside the uterus. The most widely accepted theory for endometriosis development, retrograde menstruation, does not account for extra-pelvic lesions or ones found on other organs in the peritoneal cavity. Similar to ovarian cancer, endometriosis cells can interact with the mesothelial cells of the peritoneal cavity. In ovarian cancer metastasis, ovarian cancer cell spheroids attach and push away the mesothelial cells lining the peritoneal cavity, clearing the mesothelial layer. Since endometriosis cells are known to interact with the mesothelium, we hypothesized that endometriosis cells would be able to form spheroids capable of undergoing mesothelial clearance. To test this, we designed an in vitro mesothelial clearance assay using endometriosis spheroids and a mesothelial cell monolayer. Our results demonstrate that normal and endometriotic epithelial cell spheroids can perform mesothelial clearance similar to ovarian cancer spheroids, though normal endometrial cells do not clear as well as endometriosis cells. Additionally, we demonstrated that our mesothelial clearance assay can test potential pharmacological therapies for endometriosis prior to clinical trials. These results give insight into the development of endometriosis lesions, but further research is needed to determine the mechanisms behind mesothelial clearance in endometriosis.